2021
DOI: 10.1101/2021.04.08.438850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The methyl phosphate capping enzyme Bin3 is a stable component of the fission yeast telomerase holoenzyme

Abstract: The telomerase holoenzyme is critical for maintaining eukaryotic genome integrity. In addition to a reverse transcriptase and an RNA template, telomerase contains additional proteins that protect the telomerase RNA and promote holoenzyme assembly. Here we report that the methyl phosphate capping enzyme (MePCE) Bin3 is a stable component of the S. pombe telomerase holoenzyme. Bin3 associates with the telomerase holoenzyme and the U6 snRNA through an interaction with the recently described LARP7 family member P… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…To our knowledge, this is the first example of a member of the LARP7 family functioning in a complex with MePCE/Bin3 outside the 7SK complex, indicating that the functional association of these two proteins predates the metazoan invention of the 7SK RNP as a transcriptional and translational regulator. Coincidentally, RIP-Seq experiments with epitope-tagged Bmc1 (Bin3) also identified TER1 as a target leading to an independent characterization of the Bmc1/Pof8 interaction by the Bayfield group 42 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first example of a member of the LARP7 family functioning in a complex with MePCE/Bin3 outside the 7SK complex, indicating that the functional association of these two proteins predates the metazoan invention of the 7SK RNP as a transcriptional and translational regulator. Coincidentally, RIP-Seq experiments with epitope-tagged Bmc1 (Bin3) also identified TER1 as a target leading to an independent characterization of the Bmc1/Pof8 interaction by the Bayfield group 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Using Northern blot and RT-qPCR assays, we showed that the levels of various tRNA and miRNAs are not affected by amus mutations (Figure S4A, B, C). The pombe Bmc1 protein has been shown to be important for telomere length homeostasis by interacting with the telomerase RNA substrate (Páez-Moscoso et al 2022;Porat et al 2022), we therefore measured telomeric transcription in amus mutants but did not observe any significant change (Figure S4D). Therefore, loss of Amus seems to specifically affect the steady state level of U6 snRNA.…”
Section: Amus Is a Nuclear Protein That Interacts With And Controls T...mentioning
confidence: 96%
“…Despite these results suggesting MePCE is the capping enzyme for U6, neither the partial loss of MePCE in mammalian cells nor the complete loss of Bin3 in Drosophila affects cellular U6 levels (Jeronimo et al 2007;Singh et al 2011). More recently, two groups carried out independent studies of the Bin3/MePCE homologous Bmc1 protein in S. pombe, an organism that lacks 7SK but depends on U6 for pre-mRNA splicing (Páez-Moscoso et al 2022;Porat et al 2022). Although U6 association with Bmc1 has been established in one study, both groups concluded that the loss of Bmc1 has no effect on U6 level.…”
Section: Introductionmentioning
confidence: 99%